3. Quita paréntesis y resuelve.
a) 6(x + 1) - 4x = 5x – 9
b) 18x - 13 = 8 - 4(3x - 1)
c) 3x + 5(2x - 1) = 8 – 3(4 - 5x)
d) 5 – (4x + 6) = 3x + (7 – 4x)
e) x – 7(2x + 1) = 2(6 – 5x) – 13
f) 11-5(3x + 2) + 7x = 1 - 8x
g) 13x – 5(x + 2) = 4(2x – 1) + 7
Ayudaaaa
Respuestas
Respuesta dada por:
3
Respuesta:dame coronita pliss =)
Explicación paso a paso:
a)6x+6-4x=5x-9
2x+6=5x-9
2x-5x=-9-6
-3x=-15
x=-5
b)18x-13=8-12x+4
18x -13=12-12x
18x+12x=12+13
30x=25
x= 5/6
Preguntas similares
hace 2 años
hace 2 años
hace 2 años
hace 5 años
hace 5 años
hace 7 años
hace 7 años